The comparison and use of tools for quantification of antimicrobial use in Indonesian broiler farms - Anwar Sani, Rianna; Wagenaar, Jaap A.; Dinar, Tagrid E. H. A.; Sunandar, Sunandar; Nurbiyanti, Nofita; Suandy, Imron; Pertela, Gian; Jahja, Elvina J.; Purwanto, Budi; , CORNERSTONE group; Geijlswijk, Ingeborg M. van; Speksnijder, David C.; et al. (Frontiers in Veterinary Science, 2023)
Indonesia has a large broiler industry with extensive antimicrobial use (AMU) according to empirical evidence. However, there are no quantitative data of on-farm AMU. Quantification of AMU at farm level is crucial to guide interventions on antimicrobial stewardship (AMS). The objective of this study was to compare on-farm AMU monitoring methods, to assess which monitoring method is best suited to gain insight in the quantitative AMU at farm level in medium-scale Indonesian broiler farms. AMU was calculated using four different indicators – mg/PCU (mass-based), TFUDDindo (Treatment Frequency of Used Daily Dose, dose-based), TFDDDvet (Treatment Frequency of Defined Daily Dose, dose-based) and TFcount-based (count-based) – for the total AMU of 98 production cycles with an average length of 30 days. Broilers were exposed to an average of 10 days of antimicrobial treatments per production cycle, whereas 60.8% of the antimicrobials belonged to the Highest Priority Critically Important Antimicrobials (HPCIAs). For each pair of indicators, the Spearman rank correlation coefficient was calculated to assess if the production cycles were ranked consistently in increasing AMU across the different indicators. The correlation varied between 0.4 and 0.8. This study illustrates the considerable difference in the ranking of AMU between the different indicators. In a setting comparable to medium-scale broiler farms in Indonesia, where resources are scarce and there is no professional oversight, the TFcount-based method is best suitable. Before implementing an AMU monitoring method, carefull consideration of the use-indicators is paramount to achieve fair benchmarking.